Sufficiency, change, and flexibility: Critically examining the energy consumption profiles of solar PV prosumers in Sweden. (May 2018) - Palm, Jenny; Eidenskog, Maria; Luthander, Rasmus
Highlights: We study the consumption flexibility of households producing electricity in Sweden. We found no general behavioural change, but big variations between households. Installing PVs led to increased awareness of the energy system. Households thought the benefits of shifting their electricity load were minimal. Some saw PV production as free electricity, leading to increased consumption. Abstract: The number of consumers producing electricity at home, i.e., "prosumers", is rapidly increasing in many European countries. This article analyses the electricity consumption and energy-saving behaviours of households that own photovoltaic (PV) systems in Sweden. Earlier studies of how home production of electricity affects consumption patterns are few and their results are mixed. We interviewed prosumers in Sweden and collected electricity-consumption data one year before and after they installed PVs. The differences between households were large and no general behavioural change could be detected. The interviews indicated that awareness of the energy system increased among all prosumers, but led to no substantial changes in how or when activities were performed. Most prosumers thought that the benefits of shifting their electricity load to other times were too small. The changes prosumers did make mostly concerned smaller adjustments. Households that increased their consumption justified this by their access to "free" electricity. Automation, i.e., using a timer, was relatively unknown or not used when known.